Optimising implementation strategies of the first scaleup of a primary care psychological intervention for common mental disorders in Sub-Saharan Africa: a mixed methods study protocol for the optimised Friendship Bench (OptFB) - Andy Healey; Dixon Chibanda; Ricardo Araya; Ruth Verhey; Charmaine Chitiyo; Sandra Ngonidzashe Mboweni; Ephraim Chiriseri; Bradley Wagenaar (BMJ Open)
Introduction Common mental disorders (CMDs) are a leading cause of disability globally. CMDs are highly prevalent in Zimbabwe and have been addressed by an evidence-based, task-shifting psychological intervention called the Friendship Bench (FB). The task-shifted FB programme guides clients through problem-solving therapy. It was scaled up across 36 implementation sites in Zimbabwe in 2016.Methods and analysis This study will employ a mixed-method framework. It aims to: (1) use quantitative survey methodologies organised around the Reach, Effectiveness, Adoption and Implementation and Maintenance evaluation framework to assess the current scaleup of the FB intervention and classify 36 clinics according to levels of performance; (2) use qualitative focus group discussions and semistructured interviews organised around the Consolidated Framework for Implementation Research to analyse determinants of implementation success, as well as elucidate heterogeneity in implementation strategies through comparing high-performing and low-performing clinics; and (3) use the results from aims 1 and 2 to develop strategies to optimise the Friendship Bench intervention and apply this model in a cluster randomised controlled trial to evaluate potential improvements among low-performing clinics. The trial will be registered with the Pan African Clinical Trial Registry (www.pactr.org). The planned randomised controlled trial for the third research aim will be registered after completing aims one and two because the intervention is dependent on knowledge generated during these phases.Ethics and dissemination The research protocol received full authorisation from the Medical Research Council of Zimbabwe (MRCZ A/242). It is anticipated that changes in data collection tools and consent forms will take place at all three phases of the study and approval from MRCZ will be sought. All interview partners will be asked for informed consent. The research team will prioritise open-access publications to disseminate research results.